2002
DOI: 10.1021/ma011807u
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Dynamics of Atactic Polypropylene As Revealed by Molecular Simulations and Quasielastic Neutron Scattering

Abstract: The dynamics of atactic polypropylene has been explored with quasielastic neutron scattering (QENS) measurements in the temperature range 4-460 K and momentum transfer range q) 0.2-2.25 Å-1. In parallel, molecular dynamics simulations of the same polymer have been conducted in the temperature range 260-600 K, using both a fully atomistic model and a model with united-atom methyl groups. In conjunction with the second model, a computational procedure for introducing the motion of methyl hydrogens a posteriori i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 44 publications
8
62
1
4
Order By: Relevance
“…As W 0 eff ϳ N −0. 4 , the values estimated of Wb 4 slightly change with N ͑M w ͒. However, they perfectly agree in the average with the experimental value deduced from neutron scattering measurements at 492 K.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As W 0 eff ϳ N −0. 4 , the values estimated of Wb 4 slightly change with N ͑M w ͒. However, they perfectly agree in the average with the experimental value deduced from neutron scattering measurements at 492 K.…”
Section: Discussionsupporting
confidence: 83%
“…This figure also includes two low temperature values of Wb 4 estimated from incoherent neutron scattering results on a PEP sample of M w Ӎ 20 000 g / mol. 36 From the simulation results reported here, we can also calculate Wb 4 as the large N / p-limit of W eff b 4 . In that regime both W eff ͑W 0 eff ͒ and b are basically constant.…”
Section: Discussionmentioning
confidence: 84%
“…This assumption is confirmed (see e.g., [85][86][87][88]) by molecular dynamics simulations (MDS), which allow one to observe the motion of each individual methyl group in the system. Fig.…”
Section: Classical Hoppingmentioning
confidence: 83%
“…Though the RRDM was initially developed for polymer systems, it must be stressed that all its basic assumptions can, in principle, be also applied to non-polymeric disordered systems (see Section VII). In the framework of the RRDM [25,[31][32][33][34][35][36][88][89][90][91][92][93][94], it is assumed that the only effect of the structural disorder on methyl group dynamics is to introduce a distribution of rotational barriers g(V 3 ), originated from the different local environments felt by the individual methyl groups. A non-trivial assumption is that the distribution of distances between neighbouring methyl groups does not introduce significant coupling forces for the smallest distances, which, in particular, would modify the single-particle Hamiltonian (9) leading to a more complex energy level scheme [95][96][97][98][99][100].…”
Section: Methyl Group Dynamics In Polymer Systems a Rotation Ratmentioning
confidence: 99%
“…The distribution of relaxation times was determined by analysing segmental self-diffusion in a number of small regions of the model lattice, as explained below. These distributions have been calculated in other studies by means of Molecular Dynamics [7,8], but to our 4 knowledge this is the first time that this problem has been analyzed by the BFM. Model simulations showed that the distribution shifted toward longer times as the temperature decreased while broadening [9].…”
Section: -Introductionmentioning
confidence: 99%